Availability of results of academic randomized trials involving cooperative groups in oncology in France: A systematic search of clinical trial registries. (September 2022) - Créquit, Perrine; Vivot, Alexandre; Grégory, Jules; Milleron, Bernard
Abstract: Background: Cooperative groups' involvement is increasing in academic oncological research. We aimed to assess the impact of sponsoring by cooperative groups in France on the availability of results of academic randomized trials in oncology. Methods: We performed a systematic search using ClinicalTrials.gov and the European Clinical Trials Register. We searched for all academic randomized trials in oncology conducted in France between January 1, 2005 and January 1, 2015. The inclusion criteria were: completed or terminated, phase 2 or 3 randomized trials with an academic (non-industry) sponsor. The main outcome was the publication of the results of trial (either as a journal article or as posting results in a registry) across each type of sponsor. Results: We included 211 randomized trials, mainly phase 3 (n = 135, 64%) and evaluating pharmacological treatments (n = 149, 71%). French cooperative groups were involved in 69 trials (33%), as part of a collaboration in one third (n = 23) of instances. Seventy-one (34%) trials were run by oncologic hospitals, 50 (23%) by university hospitals, and 21 (10%) by European organizations. Seventy-seven randomized trials (36%) had available results (published n = 73, posted n = 6). Cooperative groups were involved in half of those that have been published (37/73). The cumulative probability of results availability was 57% for cooperative groups, 41% for European organizations, 32% for oncologic hospitals, and 17% for university hospital at 10 years from the beginning of trials (p = 0.0006). In the case of collaboration with cooperative groups, the cumulative probability of results availability achieved 59% for university hospitals and 74% for oncologic hospitals. Conclusion: The availability of results of randomized trials in oncology remains limited and almost exclusively through publications, but is higher when cooperative groups are involved. Policy summary: Sponsoring by a cooperative group should become the rule in academic trials to increase availability of trial results. Highlights: Cooperative groups' involvement in randomized clinical trial is more and more common Trials sponsored by a cooperative group were published more often and in journals with higher impact factors. Collaboration with cooperative groups appears to be favorable for the dissemination of trial results.